Constructing Space and Self through Risk Taking: A Case of Asian Solo Female Travelers. (February 2018) - Yang, Elaine Chiao Ling; Khoo-Lattimore, Catheryn; Arcodia, Charles
In response to the increasingly risk-conscious environment in contemporary society, a growing body of literature has been dedicated to tourist risk perception. While risk is widely assumed to be a negative element in tourism, this perspective overlooks the fact that risk and tourist experience are intrinsically connected. This study takes a different approach by focusing on tourist risk-taking behavior, specifically, the risk perception and risk management of Asian solo female travelers, with an aim to contribute theoretical insights to the partial, conventional understanding of tourism risk. Located within a feminist framework, this study reveals how existing tourism space remains gendered and Western-dominated, how Asian women grapple with risks through various gendered spatial and bodily practices, and how negotiating risk is also a way to negotiate gender identities. A number of recommendations are provided for future research and for the tourism industry to foster a friendlier space for the Others .